Association of socioeconomic status change between infancy and adolescence, and blood pressure, in South African young adults: Birth to Twenty Cohort. Issue 3 (30th March 2016) - Kagura, Juliana; Adair, Linda S; Pisa, Pedro T; Griffiths, Paula L; Pettifor, John M; Norris, Shane A
Abstract : Objective: Social epidemiology models suggest that socioeconomic status (SES) mobility across the life course affects blood pressure. The aim of this study was to investigate the association between SES change between infancy and adolescence, and blood pressure, in young adults, and the impact of early growth on this relationship. Setting: Data for this study were obtained from a 'Birth to Twenty' cohort in Soweto, Johannesburg, in South Africa. Participants: The study included 838 Black participants aged 18 years who had household SES measures in infancy and at adolescence, anthropometry at 0, 2, 4 and 18 years of age and blood pressure at the age of 18 years. Methods: We computed SES change using asset-based household SES in infancy and during adolescence as an exposure variable, and blood pressure and hypertension status as outcomes. Multivariate linear and logistic regressions were used to investigate the associations between SES change from infancy to adolescence, and age, height and sex-specific blood pressure and hypertension prevalence after adjusting for confounders. Results: Compared to a persistent low SES, an upward SES change from low to high SES tertile between infancy and adolescence was significantly associated with lower systolic blood pressure (SBP) at the age of 18 years (β=−4.85; 95% CI −8.22 to −1.48; p<0.01; r 2 =0.1804) after adjusting for SES in infancy, small-for-gestational-age (SGA) and weight gain. Associations between SES change and SBP were partly explained by weight gain between birth and the age of 18 years. There was no association between SES mobility and diastolic blood pressure, mean arterial pressure or hypertension status. Conclusions: Our study confirms that upward SES change has a protective effect on SBP by the time participants reach young adulthood. Socioeconomic policies and interventions that address inequality may have the potential to reduce cardiovascular disease burden related to BP in later life.